Mapping of Patents Related to The Development of Products for Diabetic Neuropathy: a technological prospection from 2010 to 2022 (Research, Society and Development, 2022)
Diabetic neuropathy is a complication of diabetes that occurs in 40-60 million diabetics worldwide and is associated with other chronic diseases. Besides that, there are no prospective studies that present the state of the technique about technologies developed to circumvent this important public health problem. Given the above, this study aims to carry out a technological prospection about the products developed for diabetic neuropathy in the period 2010-02/02/2022. To this end, a technological prospection was carried out at the INPI and ESPACENET patent office’s always making a parallel between Brazilian reality in comparison with international companies. Therefore, in this period, it was found that the countries that produced the most patents on the subject were China, the United States, and Japan, and the company that published the most patents in this period was Beijing Luyuan Qiuzheng Technology Dev. Co Ltd. Thus, the data from this study showed that Brazil did not produce patents on the subject in this period and that China, the United States, and Japan were the countries that showed the greatest interest in technological development aimed at this disease, which affects millions of people all over the world.